2016
DOI: 10.1021/acs.organomet.6b00538
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Induced Dimerization of Alkyl-Manganese(II) 2,6-Bisiminopyridine Complexes: Selective Synthesis of a New Ditopic NNN-Pincer Ligand

Abstract: The outcome of the reaction of manganese(II) dialkyls with 2,6-bisiminopyridine (BIP) ligands is dramatically altered by the presence of very small amounts of oxygen (< 0.5 mol %), leading to binuclear species. These arise from the dimerization of the initial product, a Mn(II) 4-alkyl-2,6-bisiminodihydropyridinate alkyl complex. Cleavage of the binuclear Mn products with methanol affords the free dimeric bases, which can be regarded as a special type of ditopic NNN pincer ligand with an unusual tricyclic frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The latter was formed by C−C coupling between the 3 positions and the 5 positions of 12‐C4 followed by protonation at the 6 positions. As previously found for the products from PDI dimerization, [33–35] the 3, 4, and 5 positions of the coupled rings defined a cyclohexane ring in a chair configuration. As a result of the selective 3–3 and 5–5 C−C bond formation, the tetradentate N‐chelate adopted a U‐shaped configuration.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The latter was formed by C−C coupling between the 3 positions and the 5 positions of 12‐C4 followed by protonation at the 6 positions. As previously found for the products from PDI dimerization, [33–35] the 3, 4, and 5 positions of the coupled rings defined a cyclohexane ring in a chair configuration. As a result of the selective 3–3 and 5–5 C−C bond formation, the tetradentate N‐chelate adopted a U‐shaped configuration.…”
Section: Resultssupporting
confidence: 73%
“…Dimerization of pyridyldiimine (PDI) ligands triggered by intramolecular alkyl migration to the pyridyl ring has been reported in manganese(II), [33] aluminium(III), [34] and chromium(II) [35] alkyl complexes. An analogous transformation involving bipy was unknown and could be thought to be more energetically demanding as it involves the dearomatization of a second pyridyl ring.…”
Section: Resultsmentioning
confidence: 99%
“…However, compound 1 reacts readily with weak acids and electrophiles, as summarized in Scheme 2. We have shown before that methanol attacks at the Zn center, 17 cleanly releasing the known 1,4-dihydropyridine base 4-Bn-H2 iPr BIP. In situ NMR investigation of a similar reaction of 1 with BnOH in C6D6 in nearly 1:1 ratio revealed that the Zn-bound benzyl group ends up as toluene but did not allow to ascertain the fate of the Zn atom.…”
Section: Resultsmentioning
confidence: 96%
“…More recently, we have shown that trace amounts of oxygen suffice to trigger the dimerization pathway also in this system, leading to the corresponding Mn(II) dimers of type B. 17 Alkyl migration to the pyridine ring has also been observed when BIP ligands react with organometallic derivatives of "non-redox" main group metals. For example, Budzelaar showed that the reaction of alkylaluminum derivatives with iPr BIP produces complicated mixtures arising from non-selective alkyl migration, amongst which the corresponding C4-alkylated products of type A were detected.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation